COMPOSITE ORAL FILM BASED ON STARCH/POLY(VINYL ALCOHOL)/CHITOSAN CONTAINING Garcinia mangostana PEEL EXTRACT FOR RECURRENT APHTHOUS STOMATITIS - Ramadhani Azzahra; Sekar Asri Tresnaningtyas; Muhammad Artha Jabatsudewa Maras; Endah; Meita Mahardianti; Asy Syifa Labibah (PT. Radja Intercontinental Publishing, 2026)
Recurrent aphthous stomatitis affects approximately 5–25% of the global population, and the limited residence time of conventional topical formulations often reduces therapeutic efficacy at oral mucosal lesions. Polymeric films have emerged as promising localized oral drug delivery systems because they prolong mucosal retention and enable sustained release of bioactive compounds. Garcinia mangostana peel, an abundant agricultural by-product, is rich in xanthones, flavonoids, tannins, and phenolic compounds with antibacterial potential, although its application in oral films remains limited. This study aimed to fabricate and characterize a composite oral film based on starch/poly(vinyl alcohol)/chitosan containing Garcinia mangostana peel extract and evaluate its physicochemical properties and antibacterial activity against Streptococcus mutans. Mangosteen peel extract was prepared by maceration using 70% ethanol, cassava starch was isolated by wet extraction, and composite films containing 0%, 1%, and 2% extract were fabricated using the solvent-casting method. Mangosteen peel extraction and cassava starch isolation yielded 10% and 25%, respectively, while phytochemical screening confirmed the presence of flavonoids, saponins, tannins, and phenolic compounds. All formulations produced intact films with uniform thickness (0.260–0.268 mm), neutral pH (6.410–7.393), and folding endurance exceeding 300 cycles. Increasing extract concentration significantly enhanced antibacterial activity (p = 0.009), with inhibition zones increasing from 5.31 ± 0.19 mm (F1) to 6.66 ± 0.38 mm (F2). The 2% extract-loaded formulation exhibited the most balanced physicochemical properties and antibacterial performance, highlighting the potential of starch/poly(vinyl alcohol)/chitosan composite films as naturally derived platforms for localized oral drug delivery in recurrent aphthous stomatitis.